Benzoic acid derivatives from piper species and their fungitoxic activity against Cladosporium cladosporioides and C-sphaerospermum - Lago, JHG; Ramos, C. S.; Casanova, DCC; Morandim, A. D.; Bergamo, DCB; Cavalheiro, Alberto José [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP]; Guimaraes, E. F.; Young, MCM; Kato, M. J. (Amer Chemical Soc, 2004)
Piper crassinervium, P. aduncum, P. hostmannianum, and P. gaudichaudianum contain the new benzoic acid derivatives crassinervic acid (1), aduncumene (8), hostmaniane (18), and gaudichaudianic acid (20), respectively, as major secondary metabolites. Additionally, 19 known compounds such as benzoic acids, chromenes, and flavonoids were isolated and identified. The antifungal activity of these compounds was evaluated by bioautographic TLC assay against Cladosporium cladosporioides and C. sphaerospermum.